PROGRAM BIMBINGAN DAN KONSELING DI SEKOLAH DASAR DALAM PEMBERLAKUAN SISTEM BLENDED LEARNING - Fatihaturosyidah Fatihaturosyidah; Ima Ni’mah Chudari; Budhi Tristyanto; Esya Anesty Mashudi (As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 2023)
When SD Laboratory UPI implemented Blended learning System at post period of covid pandemic, the students perform some learning problem symptoms.  In order to prevent this, become wide spread, it is necessary to formulate a program to help students cope the problem. This research focuses on collecting empirical data of students' psychological conditions.  It will be used as base in developing program. This study takes 30 respondents to implement the DCM and the ITP instrument. The data is processed by percentage techniques and statistical tests. The results exhibit the most problems experienced by students at social problems point and indicate the students at impulsive and protection level of development tasks with the lowest aspect at the "emotional maturity", "economic behavioral independence" and "awareness of responsibility". Thus the program is designed in the composition as following: basic services to develop emotional maturity, responsive services for students with low development and problem symptoms; individual planning services with a focus on further study career planning; as well as system support in the form of in-house training in the preparation of learning kits and guidance kits.